Nano zero-valent iron and zeolite molecular sieve synergistic composite material as well as preparation method and application thereof

By using nano zero-valent iron synergistic zeolite molecular sieve composite materials, the short-range nitration-anaerobic ammonia oxidation process in the treatment of medium and low concentration ammonia nitrogen wastewater is solved, and the problems of long process start-up time and poor nitrogen removal performance are achieved, and rapid start-up and Effective nitrogen removal.

CN119430490APending Publication Date: 2025-02-14GUANGXI UNIV

Patent Information

Application Number
CN202411678757.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when treating medium and low concentration ammonia nitrogen wastewater, the short-range nitration-anaerobic ammonia oxidation process has a long start time and poor nitrogen removal performance, mainly due to the low AnAOB activity and the damage of NOB.

Method used

A composite material with nano zero-valent iron synergistic zeolite molecular sieve was prepared by impregnation method to increase the surface roughness, hydrophilicity and positive charge of the composite support, improve microbial adhesion and AnAOB activity, and inhibit NOB growth.

Benefits of technology

The rapid start of the short-range nitrification-anaerobic ammonia oxidation process is achieved, reducing the start time to 98 days, improving the total nitrogen removal rate and ammonia nitrogen removal rate, and significantly improving the economic and environmental protection of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430490A_ABST
    Figure CN119430490A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sewage control, in particular to a nano zero-valent iron and zeolite molecular sieve synergistic composite material as well as a preparation method and application thereof. The nano zero-valent iron synergistic zeolite molecular sieve composite carrier (nZVI at Z-PU) is successfully prepared through an impregnation method, the preparation method is simple and controllable, and corresponding substances are introduced in the preparation process, so that the composite carrier has the structure and properties of being rough in surface, hydrophilic and carrying positive charges. Through modification, the ammonia nitrogen adsorption capacity of the nZVI-Z-PU is increased to 4-6.5 mg / g carrier, meanwhile, the initial adsorption capacity of the nZVI-Z-PU to microorganisms is remarkably improved and is 8.7 times that of a common polyurethane sponge carrier, and the initial adsorption capacity of the nZVI-Z-PU to the microorganisms is far superior to that of the common polyurethane sponge carrier. Therefore, after the zeolite molecular sieve and the nZVI are combined, the generation of NOB can be remarkably inhibited, and meanwhile, the activity of AnAOB is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage treatment, and in particular to a composite material of nano zero-valent iron and zeolite molecular sieve, and a preparation method and application thereof. Background Art

[0002] With the acceleration of my country's urbanization process and the improvement of industrial facilities, the scale of discharge of domestic and industrial wastewater in my country's cities and towns is rapidly expanding. Among the 42 industrial sectors surveyed, the top three industries in terms of ammonia nitrogen discharge are chemical raw materials and chemical products manufacturing industry (21.5%), paper and paper products industry (10.5%), and agricultural and sideline food processing industry (10.0%).

[0003] my country is a major paper importer and exporter, and the pulp and paper industry consumes a huge amount of water. The ammonia nitrogen pollutants in papermaking wastewater generally come from two aspects. One is the addition of drugs in the production process and the conversion of nitrogen-containing substances in the raw materials themselves. When pulping, ammonium sulfite is used as a cooking agent, which will lead to high ammonia nitrogen in the papermaking wastewater. The nitrogen element contained in the pulping and papermaking plant fiber raw materials will also enter the pulping and papermaking system with the black liquor during the pulping and cooking process, forming ammonia nitrogen in the final effluent; second, the power generation equipment provided by the paper mill is generally coal-fired power generation, and selective catalytic reduction (SCR) is often used for denitrification of its flue gas. This technology requires the use of NH3 and urea mixed with water as a reducing agent, and incomplete reaction and residual reducing agent will lead to an increase in the concentration of ammonia nitrogen pollutants in papermaking wastewater.

[0004] The treatment and removal of ammonia nitrogen pollutants in wastewater is critical to the environment. The large accumulation of ammonia can have a negative impact on aquatic ecosystems, such as causing excessive growth of algae, reducing dissolved oxygen, and releasing algal toxins, leading to the death of aquatic organisms. At the same time, the quality of ammonia-containing water can also seriously affect human health. In addition to ammonia, another nitrogen-containing pollutant in wastewater is nitric acid and nitrite, which have an inhibitory effect on the growth of most microorganisms and can also have adverse effects on the health of humans, animals and plants. Therefore, it is crucial to remove nitrogen-containing pollutants in wastewater. Stringent emission limits and environmental regulations are forcing more and more industries to explore sustainable and economical methods to eliminate ammonia and nitrogen-containing pollutants in wastewater.

[0005] In sewage treatment plants, biological treatment is generally used for nitrogen removal. In the traditional biological nitrogen removal process, the nitrogen in the sewage needs to be converted into nitrogen gas through ammoniation, nitrification and denitrification, and then removed from the water in the form of gas. The traditional nitrogen removal process has shown certain effects in reducing nitrogen pollution in water bodies, but it also has some disadvantages, mainly including: (1) aeration is usually required to promote the conversion and removal of nitrogen gas, and these processes consume a lot of electricity; (2) nitrifying bacteria require organic carbon sources as electron donors, so additional organic matter needs to be supplemented; (3) the process flow is long and management is not very convenient; (4) it occupies a large area and requires large infrastructure investment. With the increasing development of water treatment technology, traditional nitrogen removal processes are becoming less and less suitable for today's sewage treatment processes.

[0006] With the in-depth study of denitrification technology, people have a deeper understanding of denitrification processes and have discovered many new nitrogen cycle pathways. These discoveries have prompted the development and application of new biological denitrification processes. Anaerobic ammonium oxidation (Anammox) is an economical and environmentally friendly biological denitrification method. Anaerobic ammonium oxidizing bacteria (AnAOB) undergo anaerobic ammonium oxidation reactions in a unique organelle (anaerobic ammonium oxidizer) to produce NH4 + and NO2 - As an electron donor and electron acceptor, it generates nitrogen gas under the action of various enzymes to remove nitrogen. This method has received widespread attention as an effective and environmentally friendly technology, and is used to treat wastewater rich in ammonia nitrogen. The anaerobic ammonium oxidation process has the advantages of fast denitrification rate, low operating cost, small footprint, low infrastructure cost and no need to add additional carbon source. However, it requires the simultaneous presence of ammonia nitrogen and nitrite nitrogen in the influent to react, so wastewater with insufficient components needs to be supplemented, which increases the economic burden and environmental pressure.

[0007] At present, some researchers have proposed to first partially nitrify part of the ammonia nitrogen into nitrite, and then use nitrite as a stable electron acceptor to participate in the anaerobic ammonium oxidation reaction, that is, partial nitrification-anaerobic ammonium oxidation (short-range nitrification-anaerobic ammonium oxidation). Partial nitrification-anaerobic ammonium oxidation reaction is a half-reaction of the traditional nitrification reaction. AOB occurs under aerobic conditions and converts 50% of NH4 + Oxidation of NO2 -The biological reaction is the reaction. The whole process is that AOB in the short-term nitrification oxidizes half of the ammonia nitrogen in the wastewater into nitrite, and then AnAOB converts the remaining ammonia nitrogen and nitrite (provided by AOB) into nitrogen gas, thereby achieving wastewater denitrification. The nitrogen conversion pathway of this reaction involves a variety of enzymes, intermediates, and energy transfer, storage, release and other processes. In the reactor, short-term nitrification and anaerobic ammonia oxidation are generally achieved by controlling the gradient changes of parameters such as DO and pH. One of the characteristics of its realization is that the ratio of the difference in nitrate nitrogen to the difference in ammonia nitrogen is 0.11. The basic principle of short-term nitrification-anaerobic ammonia oxidation is a mixed bacterial community biofilm composed of AOB and AnAOB. ​​The interior of the biofilm can be divided into an outer aerobic zone dominated by AOB, a transitional anoxic zone, and an inner anaerobic zone dominated by AnAOB. ​​The synergistic relationship between them is used to achieve wastewater denitrification, while eliminating bacteria that have adverse effects on the reaction, such as NOB. The short-cut nitrification-anaerobic ammonium oxidation process has good advantages for treating ammonia nitrogen wastewater. Its aeration energy consumption is 55-60% of that of the traditional biological nitrogen removal process, and it almost does not require a carbon source. If a carbon source is added to remove nitrate nitrogen, the input amount is also reduced by 90% compared with the traditional process, which reduces 90% of the operating cost and saves 50% of the infrastructure area. It is economical, efficient, energy-saving and environmentally friendly. Although the short-cut nitrification-anaerobic ammonium oxidation process has many advantages, because aerobic and anaerobic bacteria are present in one reactor at the same time, the internal metabolism is very complicated, and the process has the problem of long startup time. In 2002, the world's first productive short-cut nitrification-anaerobic ammonium oxidation reactor was built in Rotterdam, the Netherlands, but its startup time was as long as 3.5 years. The main reasons for its long startup time are: (1) sludge is lost due to water scouring; (2) NOB damages the short-cut nitrification-anaerobic ammonium oxidation process; (3) AnAOB is not abundant enough.

[0008] The definition of medium and low concentration ammonia nitrogen wastewater is approximately 50-500 mg / L, but in actual treatment, medium and low concentration ammonia nitrogen wastewater is generally only in the range of 60-160 mg / L. For example, the wastewater from the papermaking industry and municipal domestic sewage mentioned above are all medium and low concentration ammonia nitrogen wastewater. Due to the limitations of its own water quality and water quantity, this type of nitrogen-containing wastewater is difficult and costly to treat during the process. In current actual projects, traditional biological denitrification processes are still widely used to treat low ammonia nitrogen wastewater. Due to the need for a carbon source, the denitrification efficiency of traditional processes is generally low. In order to achieve the treatment effect, many sewage treatment plants have adopted the method of adding traditional carbon sources such as methanol, which has increased operating costs.

[0009] The short-cut nitrification-anaerobic ammonium oxidation process is completely autotrophic, that is, it does not require the participation of a carbon source. This feature directly hits the pain point of "insufficient carbon source" in the field of sewage denitrification. Therefore, the short-cut nitrification-anaerobic ammonium oxidation technology was first applied to high-concentration ammonia nitrogen wastewater with insufficient carbon sources, such as landfill leachate, printing and dyeing wastewater, and sludge anaerobic digestion supernatant. In sewage treatment plants, sludge anaerobic digestion supernatant is commonly known as "side-flow sewage". Corresponding to the high-concentration side-flow sewage, the low-concentration sewage is also commonly known as "mainstream sewage". However, the nitrogen load in the side stream usually only accounts for 20% of the nitrogen load in the mainstream sewage. Therefore, it can be imagined that the application of short-cut nitrification-anaerobic ammonium oxidation in mainstream sewage treatment has broad prospects.

[0010] However, since AnAOB is too inactive under unfavorable conditions such as low ammonia nitrogen, and the doubling time of anaerobic ammonium-oxidizing bacteria is about 19 days, and the growth and metabolism are slow, it is difficult to ensure that the retention in the treatment system reaches the abundance required for the process function, resulting in a long process startup time and reduced denitrification performance. Therefore, insufficient retention of anaerobic ammonium-oxidizing bacteria is the current process bottleneck. Therefore, it is necessary to select substances that can enhance the activity of AnAOB in a targeted manner to realize the short-range nitrification-anaerobic ammonium-oxidizing process and break through the limiting bottleneck. Summary of the invention

[0011] The purpose of the present invention is to provide a composite material of nano zero-valent iron and zeolite molecular sieve and its preparation method and application to solve the problems existing in the above-mentioned prior art. The composite material of nano zero-valent iron and zeolite molecular sieve prepared by the preparation method provided by the present invention can quickly start the short-range nitrification-anaerobic ammonia oxidation process.

[0012] To achieve the above object, the present invention provides the following solutions:

[0013] The present invention provides a method for preparing a composite material of nano zero-valent iron and zeolite molecular sieve, comprising the following steps:

[0014] The nano-zero-valent iron and the zeolite powder are uniformly mixed to obtain zeolite-nZVI powder;

[0015] The zeolite-nZVI powder, waterborne polyurethane and PVA-polyquaternium salt-10 solution are mixed, and then impregnated, extruded, first dried, washed and second dried are performed in sequence to obtain the composite material of nano zero-valent iron and zeolite molecular sieve.

[0016] Preferably, the mass ratio of the nano zero-valent iron to the zeolite powder is 1:8.

[0017] Preferably, the mass ratio of the zeolite-nZVI powder to the aqueous polyurethane is 27:40.

[0018] Further preferably, the PVA-polyquaternium salt-10 solution is a solvent; the amount of the PVA-polyquaternium salt-10 solution used is sufficient to ensure that the zeolite-nZVI powder and the aqueous polyurethane form a homogeneous solution.

[0019] Preferably, the preparation method of the PVA-polyquaternium-10 solution comprises the steps of mixing a polyvinyl alcohol solution and a polyquaternium-10 solution to obtain the PVA-polyquaternium-10 solution;

[0020] The mass percentage of polyvinyl alcohol in the polyvinyl alcohol solution is 10%; the mass percentage of polyquaternium-10 in the polyquaternium-10 solution is 5%;

[0021] The volume ratio of the polyvinyl alcohol solution to the polyquaternium-10 solution is 10:1.

[0022] Preferably, the method for preparing nano zero-valent iron comprises the following steps:

[0023] (1) mixing FeCl3, water and a dispersant to obtain a pretreated FeCl3 solution;

[0024] (2) subjecting the pretreated FeCl3 solution to ultrasonic treatment while introducing nitrogen to obtain a deoxygenated FeCl3 solution;

[0025] (3) mixing KBH4, water and ethanol to obtain a KBH4 solution;

[0026] (4) After mixing the KBH4 solution and the deoxygenated FeCl3 solution, stirring and standing the mixture in sequence to obtain the nano zero-valent iron.

[0027] Preferably, in step (1), the mass volume ratio of the FeCl3, the water and the dispersant is 6g:50mL:2.5g; the dispersant is polyethylene glycol;

[0028] In step (3), the mass volume ratio of KBH4, water and ethanol is 4.5g:20mL:30mL.

[0029] Preferably, in step (2), the nitrogen introduction rate is 0.5 mL / min;

[0030] In step (4), the stirring time is 1 hour, the rotation speed is 400 rpm; and the standing time is 30 minutes.

[0031] The present invention provides a composite material of nano zero-valent iron and zeolite molecular sieve prepared by the above preparation method.

[0032] The present invention provides the application of the composite material of nano zero-valent iron and zeolite molecular sieve in sewage treatment.

[0033] Further preferably, the sewage is sewage containing ammonia nitrogen.

[0034] The present invention provides the use of the composite material of nano zero-valent iron and zeolite molecular sieve in a rapid start-up short-range nitrification-anaerobic ammonia oxidation process.

[0035] The present invention discloses the following technical effects:

[0036] The present invention successfully prepared a nano zero-valent iron synergistic zeolite molecular sieve composite carrier (nZVI@Z-PU) by an impregnation method. The preparation method is simple and controllable, and by introducing corresponding substances in the preparation, the composite carrier has a rough surface, hydrophilicity and a structure and property of carrying positive charge. The modification increases the ammonia nitrogen adsorption of nZVI@Z-PU to 4-6.5 mg / g carrier. The ammonia nitrogen adsorption process is an entropy-driven process, which can release ammonia nitrogen when the external ammonia nitrogen concentration is low, and form a stable and continuous ammonia-rich microenvironment on the carrier surface. At the same time, the initial adsorption capacity of the nano zero-valent iron synergistic zeolite molecular sieve composite carrier (nZVI@Z-PU) for microorganisms is significantly increased, which is 8.7 times that of ordinary polyurethane sponge carriers, and can even reach 12 times, and the initial adsorption of microorganisms is far better than ordinary polyurethane sponge carriers. It can be seen that the combination of zeolite molecular sieve and nZVI can significantly inhibit the production of NOB and improve the activity of AnAOB.

[0037] To address the problem of slow start-up time of short-term nitrification-anaerobic ammonium oxidation in low-concentration ammonia nitrogen wastewater, the present invention adopts a composite carrier of nano zero-valent iron and zeolite molecular sieve, and achieves rapid start-up of short-term nitrification-anaerobic ammonium oxidation in only 98 days through the strategy of enhancing microbial attachment, inhibiting the growth of nitrifying bacteria (NOB), and improving the activity of heterotrophic nitrifying bacteria (AnAOB).

[0038] Moreover, in a specific embodiment of the present invention, the modified carriers (nZVI@Z-PU and ordinary polyurethane sponge carrier) were used to run a short-cut nitrification-anaerobic ammonium oxidation process in an SBR reactor. The R2 reactor with nZVI@Z-PU successfully started the short-cut nitrification-anaerobic ammonium oxidation process under low ammonia nitrogen concentration conditions within 98 days, achieving a total nitrogen removal rate of 80%, an ammonia nitrogen removal rate of 90% and a 0.2-0.3 kg-N / m 3 ·d -1TNRR; in contrast, the R1 reactor with the addition of a common polyurethane sponge carrier failed to successfully start short-range nitrification-anaerobic ammonium oxidation. nZVI@Z-PU exhibits a strong biomass immobilization capacity, with MLVSS / MLSS and biomass higher than those of the common polyurethane sponge carrier, and the surface has better film-forming properties. The Fe cation bridging of nZVI in nZVI@Z-PU increases the PN content and forms a stable biofilm agglomeration structure. In the reactor, NOB was eliminated and AOB bacteria were eluted. In the short-range nitrification stage, the ammonia-rich environment of nZVI@Z-PU inhibited the production of NOB bacteria. From the full aeration stage to the end of the experiment, the abundance of CandidatusBrocadia (typical AnAOB bacteria) remained at a higher level than that of the common polyurethane sponge carrier, indicating that AnAOB has a significant niche preference for nZVI-modified nZVI@Z-PU, thereby providing an environment more suitable for the growth of functional bacteria than the common polyurethane sponge carrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 The ferromagnetism and TEM images of nZVI; (a) is the magnetic separation image of nZVI, (b) is the chain-like aggregated spherical structure of nZVI, and (c) is the periphery of the nZVI core-shell.

[0041] Figure 2 Comparison of carriers before and after modification; the left side is ordinary polyurethane sponge carrier (PU), and the right side is nZVI@Z-PU;

[0042] Figure 3 The SEM images of ordinary polyurethane sponge carrier and nZVI@Z-PU; (a)-(c) are SEM images of ordinary polyurethane sponge carrier, and (d)-(f) are SEM images of nZVI@Z-PU;

[0043] Figure 4 The elemental state and chemical composition (XPS) of nZVI@Z-PU;

[0044] Figure 5Element distribution and element content of ordinary polyurethane sponge carrier; wherein, (a) is the SEM-EDS detection diagram of element C, (b) is the distribution diagram of element N, (c) is the distribution diagram of element O, (d) is the distribution diagram of element Al, (e) is the distribution diagram of element Si, (f) is the distribution diagram of element Fe, and (g) is a statistical diagram of different element contents;

[0045] Figure 6 Element distribution and element content of nZVI@Z-PU; (a) is the SEM-EDS detection diagram of element C, (b) is the distribution diagram of element N, (c) is the distribution diagram of element O, (d) is the distribution diagram of element Al, (e) is the distribution diagram of element Si, (f) is the distribution diagram of element Fe, and (g) is a statistical diagram of different element contents;

[0046] Figure 7 is the contact angle between the carrier and water before and after modification; PU-warter is the contact angle between ordinary polyurethane sponge carrier and water, and nZVI@Z-PU-water is the contact angle between nZVI@Z-PU and water

[0047] Figure 8 This is the infrared image of nZVI@Z-PU after adsorption of ammonia nitrogen; among them, nZVI@Z-PU-NH4 + Before is before nZVI@Z-PU adsorbs ammonia nitrogen, nZVI@Z-PU-NH4 + After is after nZVI@Z-PU adsorbs ammonia nitrogen;

[0048] Fig. 9 The adsorption of ammonia nitrogen by nZVI@Z-PU at different reaction temperatures; (a) is the removal rate of ammonia nitrogen, and (b) is the adsorption amount of ammonia nitrogen;

[0049] Fig.10 Linear fitting of the thermodynamic equation for the adsorption of nZVI@Z-PU;

[0050] Fig.11 Comparison of initial adsorption between nZVI@Z-PU and ordinary polyurethane sponge carrier; (a) is the surface structure diagram of nZVI@Z-PU, (b) is the surface structure diagram of ordinary polyurethane sponge carrier, (c) is the comparison of initial adsorption between nZVI@Z-PU and ordinary polyurethane sponge carrier; Pu is ordinary polyurethane sponge carrier;

[0051] Fig.12 It is an SBR reactor and a carrier;

[0052] Fig.13 is the operation cycle of the SBR reactor;

[0053] Fig.14Changes in the carrier and the biofilm on it at each stage;

[0054] Fig.15 The change of sludge particle size on the carrier at each stage;

[0055] Fig.16 The results of the effluent water quality survey; (a) is the R1 Phase I survey result, (b) is the R2 Phase I survey result, NH4 + -inf is the influent NH4 + Mass concentration, NH4 + -eff is effluent NH4 + Mass concentration, NO2 - -inf is the influent NO2 - Mass concentration, NO2 - -eff is the effluent NO2 - Mass concentration;

[0056] Fig.17 is the change of AOR, NOR, ARR and TNRR during the experimental period; where (a) is the change of AOR and NOR during the experimental period, (b) is the change of ARR and TNRR during the experimental period, AOR is the ammonia oxidation rate, NOR is the nitrite oxidation rate, ARR is the ammonia removal rate, and TNRR is the total nitrogen removal rate;

[0057] Fig.18 The results of the analysis of microbial community structure at the phylum level;

[0058] Fig.19 The abundance of microorganisms in seed mud and different reactors in stage I, where (a) is a heat map of microorganism abundance in seed mud and different reactors in stage I, and (b) is a relationship diagram between samples and species;

[0059] Fig. 20 The abundance of microorganisms in different reactors in stage III, where (a) is the heat map of microbial abundance in different reactors in stage III, and (b) is the relationship diagram between samples and species. DETAILED DESCRIPTION

[0060] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0061] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0062] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0063] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0064] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0065] Example 1 Preparation and Characterization of Nano Zero-Valent Iron@Zeolite Molecular Sieve Composite Support (nZVI@Z-PU)

[0066] 1. Preparation of nano zero-valent iron@zeolite molecular sieve composite carrier (nZVI@Z-PU)

[0067] 1.1 Synthesis of nano-zero-valent iron (nZVI)

[0068] The preparation process of nZVI needs to be carried out under the anaerobic protection of a continuous nitrogen flow. The deionized water and anhydrous ethanol used in the experiment must first be purged with nitrogen for 1 hour to remove the oxygen therein.

[0069] nZVI is prepared by an improved liquid phase reduction method. The method for preparing nZVI is as follows:

[0070] (1) 6 g of anhydrous FeCl3 was dissolved in 50 mL of deionized water, 2.5 g of polyethylene glycol was added as a dispersant, and a uniform solution was obtained by stirring. The pH value of the initial solution was adjusted to 4 with hydrochloric acid to ensure that FeCl3 would not precipitate due to the high pH value, thereby obtaining a treated FeCl3 solution.

[0071] (2) The treated FeCl3 solution was added to a three-necked flask and ultrasonically vibrated for 10 min. At the same time, nitrogen was introduced from one of the openings of the three-necked flask at a rate of 0.5 mL / min.

[0072] (3) Dissolve 4.5 g KBH4 in 20 mL deionized water and 30 mL analytical grade anhydrous ethanol, add to the constant pressure funnel, and slowly add to the other end of the three-necked flask. Keep stirring at 400 rpm throughout the reaction.

[0073] (4) After the addition is completed, the mixture is stirred at 400 rpm for 1 hour, and then allowed to stand for 30 minutes to ensure the complete growth of nZVI particles. The mixture is then taken out and sealed in a vacuum seal for subsequent experimental studies.

[0074] 1.2. Preparation of nano zero-valent iron@zeolite molecular sieve composite carrier (nZVI@Z-PU or nano zero-valent iron zeolite molecular sieve composite material)

[0075] The zero-valent iron@zeolite molecular sieve composite carrier was synthesized by impregnation method, and zeolite powder (<10 μm) and nZVI uniformly dispersed by ultrasound were fully mixed in a mass ratio of 8:1 to obtain zeolite-nZVI powder;

[0076] Then, a certain amount of polyvinyl alcohol (PVA) was dissolved in deionized water at 95° C. to prepare a 10% (w / v) PVA solution, and mixed with a 5% (w / v) polyquaternium-10 solution at a volume ratio of 10:1 to obtain a PVA-polyquaternium-10 solution;

[0077] Zeolite-nZVI powder and aqueous polyurethane are mixed in a mass ratio of 27:40, and PVA-polyquaternium-10 solution is added to form a homogeneous solution. After 5 times of immersion and extrusion, it is dried at room temperature for 24 hours. After drying, it is washed with deionized water for 3 times and dried at room temperature for 24 hours. After drying, nZVI@Z-PU is obtained and sealed in a vacuum sealed bag for storage.

[0078] 2. Characterization of nZVI@Z-PU

[0079] 2.1 Electron microscopy analysis

[0080] The size and microscopic morphology of the prepared nZVI were observed using a transmission electron microscope (TEM), and the effect captured by TEM was more obvious. nZVI was ultrasonically dispersed in anhydrous ethanol, and 2 drops of the dispersed suspension were dropped on a copper grid, and then observed on an electron microscope after natural air drying.

[0081] In order to understand the difference before and after the composite carrier is prepared, observe the dispersion of nZVI on nZVI@Z-PU, and verify whether the composite modification of the material is successful, the prepared nZVI@Z-PU and ordinary polyurethane sponge carriers are analyzed by field emission scanning electron microscopy. After the nZVI@Z-PU and ordinary polyurethane sponge carriers are washed three times with ionized water and anhydrous ethanol respectively and dried thoroughly, conductive glue is pasted on the sample plate of the field emission scanning electron microscope, and the cut nZVI@Z-PU samples and ordinary polyurethane sponge carrier samples are fixed on the sample stage with conductive glue, and then gold is sprayed to increase the conductivity of nZVI@Z-PU. After being put on the machine, the morphology is observed at different magnifications.

[0082] 2.2 Element and structure analysis of nZVI@Z-PU

[0083] XPS was used to further analyze the elemental state and chemical composition of nZVI@Z-PU, and SEM-EDS was used to detect the elemental distribution of nZVI@Z-PU and ordinary polyurethane sponge carrier.

[0084] 2.3. Contact angle measurement

[0085] The hydrophilicity of the surface modification of the carrier material plays a key role in the initial attachment of microorganisms to the carrier. The carrier surface needs to be hydrophilic and positively charged to enhance the formation of biofilm. Therefore, the contact angle experiment was used to study the hydrophilicity of nZVI@Z-PU.

[0086] 3. Results

[0087] 3.1 Morphological characterization of nZVI and nZVI@Z-PU

[0088] nZVI particles were prepared by an improved liquid phase reduction method. Figure 1 As can be seen from (a) in the figure, the obtained black powder can be separated by magnetic field and has ferromagnetism, which is preliminarily inferred to be nZVI. Combining the ferromagnetism of nZVI and the TEM image ( Figure 1 (b) of the figure studies the morphology of the materials used. It can be seen that the prepared materials have a nano-spherical structure and a high tendency to agglomerate. The nanoparticles have a chain-like aggregation structure, which is caused by their inherent magnetism and electrostatic interaction. The synthesized nZVI particle size is 50-110nm, indicating that they are synthesized at the nanoscale. A single particle of nZVI consists of a dense core surrounded by a thin shell. After further magnification, Figure 1As can be seen from (c) in the figure, it has a unique core-shell structure. This is because nZVI has active chemical properties, especially the iron atoms on the outside. In its core-shell structure, there is an iron core inside and the outer protective shell may be covered with a passivation layer of iron oxide, which is also a feature of nZVI.

[0089] Ordinary polyurethane sponge carrier and nZVI@Z-PU Figure 2 As shown in the figure, nZVI@Z-PU is still a small cube of 1mm×1mm×1mm, the carrier porosity is about 96%, and the composite carrier is dark black. SEM images of nZVI@Z-PU and ordinary polyurethane sponge carriers are taken. Figure 3 Scanning electron micrographs of a normal polyurethane sponge support and nZVI@Z-PU are shown. Figure 3 From (a)-(c) in the figure, it can be seen that the common polyurethane sponge carrier mainly has a hole-frame structure, and the sponge skeleton of the common polyurethane sponge carrier is relatively smooth without other branches. Figure 3 (d)-(f) show the scanning electron micrographs of nZVI@Z-PU. The sponge skeleton is obviously transformed from a smooth polyurethane structural scaffold to a polyurethane structural scaffold loaded with a large number of particles and containing many extremely rough branches. Figure 3 As can be seen from the local detail image (f), due to the loading of zeolite powder and nZVI, the surface of the carrier of nZVI@Z-PU is no longer as smooth as before but becomes uneven, resulting in a larger surface roughness. The rough surface is beneficial to resist hydraulic shear in the initial adhesion stage of microorganisms, and a larger viscosity is generated between the biofilm and the carrier surface. The larger viscosity can effectively prevent the loss of biomass caused by hydraulic erosion, effectively enrich microorganisms, and thus make the biofilm on the surface form faster.

[0090] 3.2 Element and structure analysis of nZVI@Z-PU

[0091] The elemental state and chemical composition of nZVI@Z-PU were further analyzed by XPS, such as Figure 4 As shown, Fe 2P from nZVI, Si 2p and Al 2p from zeolite, as well as O1s, C1s and N1s of the polyurethane itself as a matrix can be observed in the full spectrum, which once again confirms that nZVI and zeolite molecular sieves are successfully introduced into nZVI@Z-PU.

[0092] The element distribution of nZVI@Z-PU and ordinary polyurethane sponge carrier was detected by SEM-EDS. The element distribution of ordinary polyurethane sponge carrier is as follows: Figure 5As shown in the figure, it can be seen that the distribution of C, N, and O elements on the ordinary polyurethane sponge carrier is consistent with that of the polyurethane sponge skeleton. This is because C, N, and O are components of polyurethane, and their mass percentages are 72.16%, 6.04%, and 20.83%, respectively. However, Al, Si, and Fe are very rare in ordinary polyurethane sponge carriers. The element distribution diagram of nZVI@Z-PU is shown in the figure. Figure 6 As shown in the figure, it can be seen that due to the successful loading of nZVI and zeolite, the Al, Si, and Fe elements are significantly more than those of ordinary polyurethane sponge carriers, and the mass percentages rise to 1.41%, 1.55%, and 4.58%. In addition, the element distribution of Al, Si, and Fe is consistent with the distribution of the polyurethane sponge skeleton, which shows that in the synthesis of nZVI@Z-PU, nZVI and zeolite are evenly distributed, and spherical nanoparticles of similar size and zeolite particles are evenly dispersed on the surface and gaps of the sponge carrier.

[0093] In order to explore whether the composite carrier (nZVI@Z-PU) still has the ability to adsorb ammonia nitrogen, the composite carrier was soaked in a sufficient amount of ammonia nitrogen solution for 6 hours, then taken out, washed repeatedly with deionized water, dried, and ground into powder with the original sponge carrier by liquid nitrogen freezing and sieving. The material was analyzed by Fourier transform infrared spectrometer (FT-IR). Before the experiment started, the potassium bromide to be used in the experiment was baked at 150°C for 12 hours in advance. All utensils were wiped with anhydrous ethanol and operated in front of the oven to avoid moisture absorption. The sample and KBr were mixed and ground at a ratio of 0.1wt%, and pressed into thin sheets after sufficient grinding. The thin slices were tested on the machine with a scanning wavelength of 250nm-4000nm.

[0094] 3.3. Contact angle measurement

[0095] The contact angle of the carrier to water before and after modification was studied for 20 seconds. Generally speaking, a contact angle greater than 90° is hydrophobic, and a contact angle less than 90° is hydrophilic. Figure 7 The contact angle of the carrier with water before and after modification is shown. In 20 seconds, the contact angle of nZVI@Z-PU with water changed from 95.7° to 65.9°, reflecting its hydrophilic nature, while the ordinary polyurethane sponge carrier has always maintained a hydrophobic state of about 116°. The carrier changed from hydrophobic to hydrophilic after modification, mainly due to the addition of two hydrophilic substances, PVA and zeolite, during production. The surface properties of the suspended carrier are one of the key factors affecting the initial adhesion of microorganisms on the carrier surface and the subsequent biofilm formation. Therefore, a carrier with a hydrophilic surface is particularly important for the initial adhesion of microorganisms. Most sponge carriers are made of hydrophobic and negatively charged polymers such as polyurethane, polyethylene or polypropylene, which are usually not conducive to the formation of biofilms.

[0096] Example 2: nZVI@Z-PU ammonia nitrogen adsorption experiment, adsorption reaction thermodynamic analysis and comparison of static adsorption of microorganisms

[0097] 1. Adsorption experiment

[0098] The adsorption experiment adopts static oscillation adsorption (refer to the experimental steps of "Research on Nitritation and Low-carbon Denitrification in Zeolite Sequencing Batch Reactor"), specifically:

[0099] Prepare ammonia nitrogen solution, weigh 200mL and pour into a 500mL conical flask, then add 20 nZVI@Z-PU or 20 ordinary polyurethane sponge carriers respectively. Oscillate with a water bath oscillator at 25°C for about 5 hours, take a water sample (2mL) every 1 hour, and use the water sample of the ordinary polyurethane sponge carrier as the blank group to measure the absorbance with a spectrophotometer. Under the same experimental conditions, change the experimental temperature and record the ammonia nitrogen concentration at which the adsorption reaches equilibrium at T = 25°C, T = 35°C, and T = 45°C. Calculate the ammonia nitrogen adsorption amount (q t ) and the ammonia nitrogen removal rate in the solution (η); the calculation formulas for ammonia nitrogen adsorption and ammonia nitrogen removal rate are as follows:

[0100]

[0101] In the formula: qt-amount of ammonia nitrogen adsorbed on the adsorbent (mg / g); c0-initial concentration of ammonia nitrogen solution (mg / L); ct-concentration of ammonia nitrogen solution at time t (mg / L); V-volume of ammonia nitrogen solution (L); M-mass of adsorbent (g).

[0102] The experiment was performed three times to make the standard error < 5%.

[0103] 2. Thermodynamic analysis of adsorption reaction

[0104] Adsorption thermodynamics is to find out whether the reaction can proceed spontaneously, to what extent it can proceed and the driving conditions of the reaction. Whether the ammonia nitrogen adsorption can spontaneously diffuse in the zeolite and complete the entire adsorption process is determined by the Gibbs free energy of the reaction. The driving force of the reaction needs to be analyzed by studying the adsorption amount of the adsorbate on the adsorption machine to obtain various thermodynamic parameters. The thermodynamic formula is as follows:

[0105]

[0106] If it is an ideal adsorption, then: ΔG = -RTlnK C =ΔH-TΔS;

[0107] Can be transformed into:

[0108] Where: c e - is the equilibrium concentration of ammonia nitrogen in the solution (mg / L); R- is the molar gas constant (8.314 J·mol -1 ·K -1); T- is the solution temperature (K); K- is the correlation constant; Kc- is the equilibrium adsorption distribution coefficient; ΔG- is the Gibbs free energy (J·mol -1 ); ΔH-enthalpy change (KJ·mol -1 ); ΔS-entropy change (J·mol -1 ·K -1 ); c0-initial concentration of ammonia nitrogen solution (mg / L); M-mass of adsorbent (g), V-volume of adsorbed solution (L).

[0109] Therefore, in order to further study the adsorption of ammonia nitrogen by nZVI@Z-PU in this example, in order to find out the spontaneity and degree of the adsorption reaction, the adsorption process at different temperatures was thermodynamically analyzed.

[0110] 3. Static adsorption experiment of nZVI@Z-PU on microorganisms

[0111] The floc suspension was improved by the preparation of sludge suspension. Fresh activated sludge was washed with 0.1M phosphate buffer, and after removing the supernatant, it was resuspended and washed three times. 5.0g of wet weight of activated sludge was weighed and dispersed in 50mL of sterile water. The sludge was vortexed on a vortex shaker for 5min, and then slightly centrifuged at 800rpm for 5min. The supernatant was removed, and 1mL of the precipitated liquid was taken and dissolved in 100ml of sterile water to prepare a 1g / L bacterial suspension.

[0112] Take 10mL of the mixed bacterial suspension and add it to a 500mL serum bottle containing 200mL of nutrient matrix. The nutrient matrix composition is: 100mgN / LNH4Cl, 100mgN / LNaNO2 as a nitrogen source, 40mg / LKH2PO4, 800mg / LNaHCO3, 36mg / LCaCl2·2H2O, 25mg / LMgCl2·6H2O, 1mL / L trace elements. Add 10 particles of nZVI@Z-PU and ordinary polyurethane sponge carrier respectively, and place the serum bottle in a water bath shaker at 30℃ and 120rpm. After 24h of dynamic adsorption, remove the adsorbed carrier with sterile tweezers. Set up three parallel groups for each reaction to analyze the static adsorption amount of the carrier surface.

[0113] After the static adsorption experiment, three carriers were taken out with sterile tweezers, and the carriers were repeatedly washed three times with sterile water. Three parallels were set up in each group, and the carriers without static adsorption were used as the control group. The amount of bacterial flocs on the surface of the carriers was measured by crystal violet staining. The washed samples were dried at 40°C for 45 minutes, and the dried samples were placed in 1% crystal violet solution for staining for 45 minutes. After staining, the samples were taken out and washed three times with sterile water. The washed samples were naturally air-dried for 6 hours, and the dried samples were placed in a 30ml centrifuge tube containing 95% ethanol solution. After vortexing for 3 minutes, the dyed bacterial flocs were separated from the carriers by ultrasound for 10 minutes, and the absorbance of the detached liquid was measured at 595nm under a UV spectrophotometer. The absorbance at 595nm was used instead of the total amount of bacterial flocs. The higher the absorbance, the more total amount of bacterial flocs attached to the surface of microplastics.

[0114] 4. Results

[0115] 4.1. Ammonia nitrogen adsorption capacity, ammonia nitrogen adsorption model and mechanism research

[0116] In the preparation of nZVI@Z-PU, an aqueous polyurethane with the same composition as the ordinary polyurethane sponge carrier was used as the adhesive matrix, and nZVI and zeolite were loaded on the sponge carrier. Therefore, the surface of the zeolite was covered with a thin layer of polyurethane film, which may affect the ammonia nitrogen adsorption of zeolite on nZVI@Z-PU. The ammonia nitrogen adsorption of nZVI@Z-PU at 25°C is shown in Figure 2. Figure 8 As shown. Figure 8 It can be seen that at 1450cm -1 There is an obvious absorption peak, which is NH4 + This shows that the coverage of the polyurethane film has no effect on the absorption of ammonia nitrogen by the zeolite carrier. It also shows that the water-based polyurethane mixed film on the surface of nZVI@Z-PU is not airtight, but has tiny holes that allow substances of specific sizes from the outside to exchange with substances in the film. At the same time, because of the presence of the polyurethane film, the subsequent microorganisms do not directly contact nZVI when adsorbed on the carrier, which also avoids the toxicity of the active oxygen generated during the oxidation of nZVI to the microorganisms.

[0117] Adsorption is the process of molecular movement. Temperature and molecular movement are closely related. Generally, as the temperature increases, the molecular movement state becomes more chaotic and the movement speed becomes faster. In this experiment, the removal efficiency of nZVI@Z-PU for ammonia nitrogen at different temperatures was investigated. Adsorption experiments were carried out at different reaction temperatures. The results are as follows: Fig. 9As shown. As the reaction proceeds, the removal of ammonia nitrogen by the composite carrier shows a trend of first increasing and then stabilizing, and the trend remains consistent at different temperatures. At the 60th minute, the adsorption of ammonia nitrogen reaches 3.8817 mg / g carrier, and then the adsorption rate slows down. At 480 minutes, the adsorption reaches 4.5028 mg / g carrier. Overall, in the initial 60 minutes of the reaction, the adsorption of ammonia nitrogen by nZVI@Z-PU shows a trend of rapid adsorption, and then the adsorption rate gradually slows down. This is because as the reaction proceeds, the metal cation sites of the zeolite in nZVI@Z-PU are continuously occupied by NH4 + The exchange leads to saturation of adsorption in the later stage, but the increase in temperature can promote the migration of ammonia nitrogen into the pores of zeolite, which is conducive to the adsorption of ammonia nitrogen. Therefore, with the increase in temperature, the removal rate and adsorption of ammonia nitrogen also increase. nZVI@Z-PU has a large adsorption capacity for ammonia nitrogen in a short time, and forms an ammonia-rich environment on the composite carrier through the adsorption and desorption equilibrium of ammonia nitrogen formed on the carrier.

[0118] 4.2 Thermodynamic analysis of adsorption reaction

[0119] In order to further study the adsorption of ammonia nitrogen by nZVI@Z-PU and to find out the spontaneity and degree of adsorption reaction, the adsorption process at different temperatures was thermodynamically analyzed. The corresponding distribution coefficient was calculated based on the thermodynamic formula, and the model was fitted to obtain the following results: Fig.10 shown.

[0120] According to the fitted thermodynamic equation, the corresponding thermodynamic parameters can be calculated and the driving conditions of the zeolite adsorption carrier process can be calculated. The results are shown in Table 1.

[0121] Table 1 Thermodynamic parameters of ammonia nitrogen adsorption by nZVI@Z-PU

[0122]

[0123] Depend on Fig.10 As shown in Table 1, the ΔH of the adsorption system is greater than 0, indicating that the adsorption of ammonia nitrogen by nZVI@Z-PU is an endothermic process, which is consistent with Fig. 9As the temperature rises, the removal rate is consistent with the increase in adsorption amount, and the increase in temperature is conducive to the reaction. ΔG<0, indicating that the adsorption process of ammonia nitrogen by nZVI@Z-PU is a spontaneous reaction process. |ΔG| reflects the driving force of the adsorption process. As the temperature rises, |ΔG| increases, and the driving force of the reaction becomes greater. During the adsorption process, ΔS>0 indicates that the adsorption process is an entropy increase process, while the adsorption reaction at the solid-liquid mixed interface is a process of accumulating substances on the solid surface, so it is usually considered to be an entropy reduction process. The difference occurs because the adsorption process of ammonia nitrogen by zeolite in the composite carrier is an ion exchange process. While ammonia nitrogen is adsorbed, the metal cations in the zeolite molecular sieve are exchanged into the solution, increasing the entropy value of the system. When the entropy reduction caused by the accumulation of ammonia nitrogen is not enough to cover the entropy increase caused by ion exchange, the entropy value of the entire system increases. ΔH>0, ΔS>0 and ΔG<0, indicating that the adsorption of ammonia nitrogen by the carrier is a typical entropy-driven process. In the entropy-driven reaction process, the system moves in the direction of increasing entropy. When the external ammonia nitrogen concentration decreases to less than the concentration in the carrier, ammonia nitrogen diffuses from the carrier to the outside, thus maintaining a high concentration buffer of ammonia nitrogen and forming a stable ammonia-rich environment on the surface. This is more beneficial for eluting NOB and enriching AOB and AnAOB. ​​Therefore, the composite carrier with high ammonia nitrogen adsorption capacity has great potential as a carrier filler for PN-A reaction.

[0124] 4.3 Comparison of static adsorption of microorganisms by carriers

[0125] The initial adsorption of microorganisms on ordinary polyurethane sponge carriers and nZVI@Z-PU was observed by scanning electron microscopy. Fig.11 As shown. Fig.11 It can be seen that compared with the smooth ordinary polyurethane sponge carrier, the surface roughness of nZVI@Z-PU is increased because it is loaded with zeolite and nZVI. This provides a site for microorganisms to hide and attach when dealing with hydraulic shear in the reactor, and they are not easily carried out of the reactor by the water flow. The initial adsorption of microorganisms is the key to the formation of biofilms. After adsorbing on the carrier, the microorganisms form nests with the rough surface grooves by secreting EPS. When the initially adsorbed microorganisms accumulate to a certain number on the carrier, the bacterial flocs are connected to each other, and the biofilm can gradually grow. Therefore, strengthening the initial adsorption is the "rate controlling step" for the formation of biofilms.

[0126] The staining of microorganisms with crystal violet can semi-quantitatively reflect the initial adsorption of microorganisms by the carrier. It can be seen that the adsorption of microorganisms by the modified nZVI@Z-PU is 8.7 times that of ordinary polyurethane sponge carriers. By comparing the carriers before and after, it can be seen that the initial adsorption of microorganisms by nZVI@Z-PU is much better than that of ordinary polyurethane sponge carriers. This is because the surface of the carrier after surface modification becomes rough, which can better provide a place for microorganisms to live. It has positive charge and hydrophilicity, which can better adsorb liquid film, and can also enhance the electrostatic attraction during the interaction between negatively charged microorganisms and carriers. This makes nZVI@Z-PU more advantageous than ordinary polyurethane sponge carriers in the initial biofilm stage.

[0127] In summary, it can be seen that, by analyzing the surface physical and chemical properties of nZVI@Z-PU in Example 1 and Example 2, nZVI and zeolite are uniformly dispersed and loaded on nZVI@Z-PU without agglomeration. At the same time, the surface roughness of nZVI@Z-PU is increased, which is beneficial to the initial adhesion stage of microorganisms. Because hydrophilic zeolite and PVA and positively charged surfactant polyquaternary ammonium salt are added during the preparation process, the improvement of the carrier surface from hydrophobic to hydrophilic is achieved. At the same time, the surface charge of the carrier is significantly increased. These changes significantly improve the adsorption capacity of nZVI@Z-PU for microorganisms, can better adsorb liquid film, and enhance the electrostatic attraction between microorganisms and carriers. Using aqueous polyurethane as a loading agent does not affect the adsorption of ammonia nitrogen by nZVI@Z-PU. nZVI@Z-PU shows the ability to rapidly adsorb ammonia nitrogen, which shows that its adsorption of ammonia nitrogen is mainly a chemical adsorption process of monolayer adsorption, and the chemical adsorption caused by chemical bond force has stronger adsorption selectivity and stability. The rough surface, positive charge and hydrophilicity of nZVI@Z-PU make its initial adsorption of microorganisms far superior to ordinary polyurethane sponge carriers. In the initial microbial adsorption experiment, the microorganisms nested in the rough surface grooves of the carrier and resisted hydraulic erosion. The crystal violet staining of the microorganisms semi-quantitatively reflected the initial adsorption of the carrier to the microorganisms. The initial adsorption of microorganisms by nZVI@Z-PU is far superior to that of ordinary polyurethane sponge carriers.

[0128] Example 3 Effect of nZVI@Z-PU on the startup of short-cut nitrification-anaerobic ammonium oxidation process

[0129] 1. Experimental materials and instruments

[0130] 1.1. Inoculation sludge

[0131] The retrieved granular sludge was crushed into flocculent sludge and mixed with the anaerobic ammonium oxidation flocculent sludge in the laboratory at a ratio of 2:1. The inoculated sludge was then stored in a refrigerator at 4°C and activated by adding nutrient solution and continuous aeration for 3 days before the start of the experiment, after which the original particle size of the sludge was measured by a laser particle size analyzer.

[0132] In view of the complexity of the actual wastewater composition, in order to ensure the stability of the experiment and to eliminate the influence of other substances as much as possible, this experiment used laboratory simulated wastewater, and the nitrogen source was provided by ammonium chloride. In order to enhance the activity of aerobic nitrifying bacteria, glucose was added to the influent within the first 10 days. Other influent matrices include: KH2PO4 (21.9 mg / L), CaCl2·H2O (36 mg / L) and MgSO4·6H2O (25 mg / L), and appropriate amounts of KOH and HCl were added to adjust the pH to 8.0-8.5. 2.5 mL of mixed trace element solution was added to each 1 L of wastewater. The mixed trace element solution was obtained by mixing trace elements I and trace elements II in a volume ratio of 1:1. The composition of trace elements I and trace elements II is shown in Table 2.

[0133] Table 2 Composition of trace elements Ⅰ and trace elements Ⅱ

[0134]

[0135]

[0136] 1.2. Drugs and instruments

[0137] The drug information is shown in Table 3, and the instrument information is shown in Table 4.

[0138] Table 3 Main experimental materials and reagents

[0139]

[0140]

[0141] Table 4 Main instruments of the experiment

[0142]

[0143] 2. Reactor Setup and Operation

[0144] Reactor and carrier Fig.12 The main body of the reactor is cylindrical organic glass, and two SBR reactors are used, with the same structure and size. The one with ordinary polyurethane sponge carrier is marked as R1, and the one with nZVI@Z-PU is marked as R2.

[0145] Oxygen is provided by an air pump through the aeration sand head at the bottom of the reactor, and the aeration volume is controlled by adjusting the rotor flowmeter. To prevent light exposure and the growth of phototrophic microorganisms from having an adverse effect on the system, the reactor is placed in an opaque black plastic barrel and heated in a water bath by an adjustable thermostatic heating rod to maintain a stable temperature to cope with changes in the external ambient temperature, thereby ensuring that the microorganisms grow and reproduce at a suitable temperature. A stirrer connected to a stainless steel rod and a three-blade stirring head is installed on the top of the reactor. All stirrers, aeration pumps, and inlet and outlet water pumps are controlled by timers.

[0146] The inlet and outlet water volume and HRT are controlled by a peristaltic pump, where one end of the inlet pipe is placed in the experimental water distribution bucket and the other end is connected to the bottom of the reactor, while one end of the outlet pipe is connected to the middle of the reactor and the other end is connected to the sludge receiving bucket for collecting the effluent sludge. During the reaction process, the simulated wastewater is transported from the water distribution bucket to the pipeline through the inlet pump, and then injected into the reactor from the bottom of the reactor. In the reactor, the wastewater is fully contacted and reacted with the sludge and biofilm carrier through aeration and stirring. After the stirring and aeration stop, the sedimentation stage begins, the carrier and sludge are precipitated at the bottom of the reactor, and the reacted wastewater flows into the sludge receiving bucket through the outlet pump.

[0147] SBR (Sequencing Batch Reactor) is commonly used in wastewater treatment and sewage treatment. It divides the treatment process into several consecutive stages. This reactor completes multiple treatment steps in a single reactor and can be adjusted as needed. It is commonly used to treat various types of wastewater and sewage, including domestic sewage, industrial wastewater, and agricultural wastewater. It has the characteristics of high efficiency, strong flexibility and good adaptability, which can save operating time and stably achieve a high total nitrogen removal rate.

[0148] The SBR reactor in this experiment includes four cycles: water inlet, aeration + stirring, sedimentation, and water outlet, and the drainage ratio is 60%. Fig.13 As shown, the steps of operation and control of the reactor are as follows:

[0149] Among them, the influent matrix concentration and the reactor operation mode were continuously adjusted according to the progress of the experiment. The operation time of the reactor was 116 days, and the entire operation period can be divided into three stages: startup period (Phase I: 1-20 days), transition period (Phase II: 21-80 days), and stable period (Phase III: 81-116 days). The specific parameters of the reactor are shown in Table 5. In the startup period of Phase I, a fixed ammonia nitrogen concentration of 110 mg-N / L was used as the influent condition, and the nitrogen load (NLR) was 0.264 kg-N / m 3 ·d -1. Continuous aeration is used to improve the activity of AOB and achieve short-range nitrification. In the transition period of Phase II, in order to improve the activity of AnAOB and maintain the activity of AOB, the aeration volume is gradually reduced to allow AOB to adapt to the environment. After entering the stable period of Phase III, in order to start PN-A under low concentration of ammonia nitrogen conditions, the ammonia nitrogen concentration of the influent is reduced to 60 mg-N / L, and the HRT is shortened to increase the NLR to 0.288 kg-N / m 3 ·d -1 When the △NO3 in the effluent of the reactor - / △NH4 + ≈0.11, the total nitrogen removal efficiency (TNRE) was greater than 70%, and the ammonia nitrogen removal efficiency (ARE) was greater than 90%, and they remained stable for a period of time, indicating that the reactor was successfully started.

[0150] Table 5 Parameter control of different stages of the reactor

[0151]

[0152] 3. Experimental methods and results

[0153] 3.1. Water quality of the reactor effluent under different carrier filling conditions

[0154] Ammonia nitrogen was detected by Nessler's reagent spectrophotometry, nitrite nitrogen was detected by ultraviolet spectrophotometry, and nitrate nitrogen was detected by thymol method. (For specific detection methods, please refer to the "Water and Wastewater Detection and Analysis Methods (Fourth Edition)" issued by the State Environmental Protection Administration) The water quality of the effluent was investigated by this method. The results are as follows Fig.16 As shown in the figure: aeration can increase the oxygen content in wastewater, improve the activity of AOB, and promote the oxidation of ammonia nitrogen. In the first stage of the reaction, a higher aeration value (0.15L / min) is used to activate the AOB in the system, obtain a larger ammonia oxidation rate and a higher nitrite accumulation rate, and lay the foundation for the subsequent short-range nitrification-anaerobic ammonia oxidation process. In the early stage of the reaction, the ammonia nitrogen in the effluent of R2 rose briefly. This abnormal phenomenon can be attributed to the additional adsorption capacity of nZVI@Z-PU for ammonia nitrogen. In a complete SBR operation cycle, the ammonia nitrogen adsorbed by nZVI@Z-PU will not be completely desorbed, and part of it will be released in the next cycle, which leads to the formation of an ammonia-rich environment on nZVI@Z-PU. As the adsorption of ammonia nitrogen by nZVI@Z-PU gradually becomes saturated, the ammonia nitrogen concentration in the effluent gradually increases.

[0155] The high aeration used in the reaction significantly enhanced the ammonia nitrogen conversion efficiency of the two reactors. However, the excessively high aeration level also led to an increase in NOB activity, resulting in the conversion of nitrite nitrogen to nitrate nitrogen. In terms of nitrite nitrogen accumulation and nitrate nitrogen removal, the nitrite nitrogen in R1 reached a peak and then dropped rapidly. At the same time, the concentration of nitrate nitrogen in the effluent continued to rise. In contrast, the nitrite nitrogen and nitrate nitrogen in the effluent of R2 remained stable, indicating that the reactor had a more stable performance. The nZVI@Z-PU in R2 showed excellent ammonia nitrogen buffering function, created an ammonia-rich microenvironment, and was able to maintain a high FA, thus becoming the main inhibitor of NOB in low-ammonia nitrogen wastewater.

[0156] 3.2 Changes in microbial activity under different carriers

[0157] Ammonia nitrogen was detected by Nessler's reagent spectrophotometry, nitrite nitrogen was detected by ultraviolet spectrophotometry, and nitrate nitrogen was detected by thymol method (for specific detection methods, please refer to the "Water and Wastewater Detection and Analysis Methods (Fourth Edition)" issued by the State Environmental Protection Administration). AOR (ammonia oxidation rate), NOR (nitrite oxidation rate) and TNRR (total nitrogen removal rate) were investigated. AOR, NOR and TNRR indirectly reflect the theoretical in situ activity of the corresponding nitrifying microorganisms. The results are as follows Fig.17 As shown in the figure: the AOR of the two reactors gradually increased in the first stage, indicating that the activity of AOB was significantly improved. nZVI@Z-PU has good initial microbial adsorption performance and the ability to construct an ammonia-rich environment, which is conducive to the enrichment of AOB bacteria. Therefore, in the early stage of the reaction, the AOR of R2 was significantly higher than that of R1. At this time, the NOR in the reactor increased, indicating that the activity of NOB began to recover, which may be due to the long-term aeration and the accumulation of nitrite providing favorable conditions for the growth of NOB. Although nZVI@Z-PU can achieve local ammonia nitrogen inhibition, the NOR of R2 did not continue to rise like R1. However, the 110 mg-N / L ammonia nitrogen wastewater in the experiment belongs to medium and low concentration ammonia nitrogen wastewater, and macroscopic inhibition cannot be achieved for the free flocculent sludge in the reactor. The TNRE of R1 and R2 has been maintained at a relatively low level, because in the short-term nitrification-anaerobic ammonia oxidation process, the removal of total nitrogen mainly depends on AnAOB bacteria, which is an anaerobic microorganism and its activity is inhibited under sufficient aeration conditions. Despite this, the TNRR of R2 is always slightly higher than that of R1. This is attributed to the fact that nZVI on the surface of nZVI@Z-PU creates a local anaerobic microenvironment through self-oxidation during aeration, which is conducive to the growth of AnAOB bacteria. The Fe ions produced by the oxidation reaction of nZVI are also one of the essential substances for the growth of AnAOB bacteria. In addition, the good initial adsorption capacity of nZVI@Z-PU for microorganisms is also one of the reasons for its high TNRR.

[0158] At the beginning of stage II, the aeration rate suddenly dropped, causing the ARR (ammonia removal rate) and AOR of the two reactors to drop sharply, and the activity of AOB was affected by low aeration. Unlike AOR, TNRR was rising slowly, indicating that the low oxygen environment was conducive to the growth of AnAOB, but the accumulation of a large amount of ammonia nitrogen in the reactor would lead to a low total nitrogen removal rate. In order to maintain the activity of AOB and AnAOB, the strategy of "gradient reduction of aeration" was adopted from the 30th day. After the change, ARR and AOR fluctuated and rose in stage II, indicating that AOB had low oxygen adaptability under oxygen fluctuation stress, and the gradual increase of TNRR also indicated that the activity of AnAOB continued to increase. The change trend of NOR in R1 and R2 was consistent with the change trend of nitrate nitrogen in the effluent, indicating that the main reason for the difference in nitrate nitrogen in the effluent was NOB bacteria. The ammonia-rich microenvironment of nZVI@Z-PU gradually eliminated NOB, showing good NOB inhibition.

[0159] In stage III, the NOR of R2 was much lower than that of R1, indicating that R2 successfully inhibited NOB. In addition, at the end of the reaction, R2 had a stronger total nitrogen removal capacity, highlighting the long-term strengthening effect of iron ions on nZVI@Z-PU on AnAOB. ​​In terms of AOB activity, although the AOR of R2 was slightly lower than that of R1, the ARR was higher than that of R1, indicating that although the number of AOB on nZVI@Z-PU in R2 was small, its unit AOB activity was higher. With the development of the biofilm, the synergistic effect between the microorganisms on the carrier of the R2 reactor continued to strengthen, making the activity of the short-range nitrification-anaerobic ammonium oxidation functional bacteria far exceed that of R1.

[0160] 3.3. Implementation of Short-cut Nitrification-Anaerobic Ammonium Oxidation Process

[0161] At the end of stage I, the ammonia nitrogen removal efficiency of R1 and R2 exceeded 90%, but the total nitrogen removal effect was not obvious. After reducing aeration in stage II, the ammonia nitrogen removal rate reached a low point, and △NO3 - / △NH4 + The ratio gradually increased, far away from the standard value of 0.11 for short-range nitrification-anaerobic ammonium oxidation reaction. After the "gradient reduction aeration", the ammonia nitrogen removal rate showed a repeated increase-decrease-and-increase process. On the 52nd day, the ammonia nitrogen removal rates of R1 and R2 reached 78% and 85%, respectively, indicating that the AOB activity was restored. At the same time, the total nitrogen in the effluent of the two reactors continued to decrease. In addition, the △NO3 — / △NH4 + The ratio is also decreasing, and the overall treatment effect of the two reactors has been significantly improved.

[0162] In the third stage, due to the decrease of influent ammonia nitrogen concentration and the decrease of HRT, the removal rate of ammonia nitrogen fluctuated to a certain extent. As the reaction progressed, the synergistic effect between microorganisms continued to strengthen. R2 successfully suppressed NOB bacteria while enriching microorganisms, resulting in the gradual washing out of the reactor of miscellaneous bacteria. By the 98th day, the △NO3 — / △NH4 + The ratio reached 0.115, close to the short-range nitrification-anaerobic ammonium oxidation standard value of 0.11. At this time, the total nitrogen removal rate was 78%, the ammonia nitrogen removal rate was 90%, and the TNRR was 0.24 kg-N / m 3 ·d -1 , successfully realizing the start-up of short-term nitrification-anaerobic ammonium oxidation under low concentration of ammonia nitrogen. In contrast, R1 did not reach △NO3 until the 116th day after the reaction. — / △NH4 + The ratio is only 0.22, the total nitrogen removal rate is 64%, the ammonia nitrogen removal rate is 88%, and the TNRR is 0.18kg-N / m 3 ·d -1 , failed to start short-range nitrification-anaerobic ammonium oxidation.

[0163] The synergistic effect of the zeolite and nZVI components in nZVI@Z-PU enables R2 to create an ammonia-rich environment in an environment with thin ammonia nitrogen, enrich AOB and AnAOB and inhibit the removal of NOB. In addition, the addition of nZVI helps to promote the synthesis of heme c in AnAOB. ​​The higher its concentration, the stronger the anaerobic ammonia oxidation activity, thereby enhancing the activity of AnAOB. ​​At the same time, the oxidation of nZVI provides an anaerobic microenvironment for the growth of AnAOB. ​​In the reactor with the addition of the composite carrier, a good synergistic effect was established between the short-term nitrification-anaerobic ammonia oxidation functional bacteria, which improved the overall performance of the reactor and enabled the short-term nitrification-anaerobic ammonia oxidation process to start quickly.

[0164] 3.4 Biofilm growth and biomass changes on carriers

[0165] The growth of biofilm on the carrier was investigated by measuring the MLSS and MLVSS in the reactor. Fig.14 As shown, Fig.14The growth of the biofilm on the carrier is shown. It was observed that the attachment of sludge to the carrier showed a trend along the sponge skeleton and gradually grew from the inside to the outside. After the reaction, the nZVI@Z-PU in R2 had formed a thick layer of sludge biofilm, and the amount of biofilm accumulated on its surface was significantly more than that of R1. The coverage of sludge made the oxygen penetration capacity inside the R2 carrier lower than that of R1. Due to the porous structure of the polyurethane sponge, microorganisms continued to attach to the internal space of the biological carrier. As the number of microorganisms attached to the carrier increased, the thickness of the biofilm also increased, which was conducive to the formation of anoxic environment inside the carrier filler, thereby promoting the Anammox process, leading to the removal of nitrogen.

[0166] The particle size of the sludge biofilm on the carrier was investigated. The specific steps were as follows: 3 biofilm carriers were randomly selected from the reactor, the sludge and carrier were separated by ultrasound, the carrier was returned to the reactor, deionized water was used as a dispersant for the obtained suspension, and then the particle size of the activated sludge was measured by a laser particle size analyzer. This process was repeated three times and the average value was taken. The results are shown in Figure 2. Fig.14 and Fig.15 As shown, Fig.15 The particle size of the sludge biofilm on the carrier at each stage is shown. As the biofilm grows, the particle size of the sludge biofilm continues to increase, and the sludge particle sizes of R1 and R2 show differences. At the end of the experiment, the sludge particle size of R2 is larger than that of R1. The higher the degree of aggregation of the sludge flocs in the biofilm, the more extracellular polymers secreted on its surface. The protein component in the extracellular polymer contains a large number of hydrophobic groups. The increase in its content will change the properties of the biofilm surface, thereby promoting the aggregation of sludge. The increase in sludge particle size can explain the increase in protein components. The polysaccharides and proteins in the extracellular polymers show a linear correlation with the biomass. Therefore, the amount of biomass can also be approximately expressed by the content of polysaccharides and proteins. R2 has better biofilm performance than R1.

[0167] 3.5. Changes in microbial abundance on carriers

[0168] Sludge samples were collected on the 20th and 100th days, respectively. The original sludge and sludge samples in different reactors were numbered Blank, R1 and R2, respectively. An appropriate amount of sludge was refrigerated and mailed to Meiji Biomedical Technology Co., Ltd. for high-throughput sequencing. The main steps of high-throughput sequencing are as follows: DNA from sludge was extracted using the EZNATM Mag-Bind Soil DNA Kit (OMEGA) kit, and bacteria and archaea were amplified using 524F10extF-Arch958RmodR and 338F-806R, respectively. The PCR product was detected by electrophoresis using a 2% agarose gel and purified using an AxyPrepDNA gel extraction kit. Finally, a PE amplicon library was sequenced based on the Ilumina Miseq platform, and the operational units (OTUs) were classified and analyzed.

[0169] The results are as follows Figure 18-Figure 20 As shown in the figure, in R1 and R2 at the end of Blank and Phase I, the relative abundances of Proteobacteria were 43.03%, 41.76% and 46.05%, respectively; the relative abundances of Chloroflexi were 22.96%, 25.58% and 20.50%, respectively; the relative abundances of Bacteroidota were 9.79%, 18.31% and 16.81%, respectively; and the relative abundances of Planctomycetota were 11.05%, 5.27% and 7.47%, respectively. This indicates that with the introduction of carriers in the reactor and the continuous aeration, the microbial community structure has undergone a certain degree of succession and elimination.

[0170] Proteobacteria has always maintained a leading position in the reactor. As the largest phylum of bacteria, its members include AOB and NOB, which are crucial to the denitrification effect of water bodies. Chloroflexi is widely present in the Anammox reactor, and a small amount of NOB also belongs to this phylum. Chloroflexi and Bacteroidota play an important role in the construction of microbial network structure, while Bacteroidota contributes to the formation of a stable biofilm skeleton. As the proportion of Bacteroidota in bacterial aggregates increases, the biofilm structure becomes more dense. [ . Compared with Blank, the abundance of Planctomycetota in R1 and R2 reactors was lower. Planctomycetota is the main phylum of AnAOB. ​​Sufficient aeration increases the oxygen content in wastewater, thereby inhibiting the growth of AnAOB bacteria. The abundance of Planctomycetota in R2 reactor is higher than that in R1, indicating that the composite carrier has better AnAOB tolerance.

[0171] At the end of stage III, Proteobacteria on R1 and R2 accounted for 28.66% and 24.40% of the total bacteria, respectively; Chloroflexi accounted for 14.96% and 16.97%, respectively; Bacteroidota accounted for 26.54% and 24.25% of the total bacteria, respectively; Planctomycetota accounted for 13.39% and 18.81% of the total bacteria, respectively. The decline of Proteobacteria and Chloroflexi may be related to the elimination of NOB in the reactor. At the same time, some AOB remaining in the flocs were washed out, which also led to the decline of Proteobacteria. The increase of Bacteroidota is related to the formation of carrier biofilm. Thanks to the action of related microorganisms in Bacteroidota, the biofilm structure on the carrier in the reactor is more compact and the biofilm grows. The growth of Planctomycetota in the total bacteria also explains the growth of AnAOB bacteria in the reactor. The proportion of Planctomycetota in R2 was 1.4 times that in R1, which also shows that the composite carrier is more conducive to the growth of AnAOB microorganisms.

[0172] The relative abundance of Denitratisoma in the seed sludge was only 0.62% at the beginning. In stage III, its relative abundance increased to 9.31% and 7.04% in R1 and R2, respectively. Denitratisoma belongs to a new genus of the family Rhodocyclaceae and was frequently detected in the PN-A reactor. In PN-A, Denitratisoma was found to use organic matter from sources such as cell lysis, decay, and soluble microbial metabolites as carbon sources and remove these decayed organic matter to prevent adverse effects on the reactor. The change of Acinetobacter experienced a process of first increasing and then decreasing. In stage I, it increased rapidly from 0.41% in the seed sludge to 18.40% and 9.74% in R1 and R2. However, in stage III, its relative abundance decreased to 0.01% and 0.06%, respectively. This change was due to the fact that Acinetobacter is an aerobic bacterium and its survival depends on oxygen. In stage I, sufficient aeration promoted the rapid growth of Acinetobacter. However, a strategy of gradually decreasing aeration was subsequently adopted, resulting in a reduction in oxygen levels in the reactor, limiting the activity of Acinetobacter and ultimately leading to its elimination.

[0173] CandidatusBrocadia is a typical AnAOB bacteria, commonly found in sewage treatment systems. Its relative abundance in the seed sludge was 7.31%. At the end of stage I, its relative abundance in R1 and R2 decreased to 3.54% and 4.26%, respectively. This decrease was due to the limitation of AnAOB bacteria caused by sufficient aeration. Fig.19 As shown in the figure, under oxygen limitation, the abundance of CandidatusBrocadia on R2 was still higher than that on R1, which shows the performance of the composite carrier in creating an anaerobic microenvironment. In stage III, CandidatusBrocadia in R1 and R2 reached 10.62% and 15.08%, respectively. The relative abundance of Candidatus Brocadia on R2 was 1.42 times that of R1. CandidatusKuenenia has a clear niche preference for iron-based modified carriers. Considering that the enrichment and maintenance of AnAOB on carriers is one of the main obstacles limiting the widespread application of PN-A, this finding confirms that AnAOB can be enriched in situ on composite carriers. Combined with the aforementioned effluent conditions, it shows that the addition of nZVI@Z-PU can maintain high AnAOB abundance and high activity in the case of low concentration of ammonia nitrogen influent.

[0174] Nitrolancea belongs to NOB bacteria, and its relative abundance in R1 and R2 in stage I was 3.41% and 2.74%, respectively. The ammonia-rich environment created by nZVI@Z-PU inhibited the growth of NOB, resulting in a lower abundance of NOB in R2 than in R1. This is also the reason why the nitrite nitrogen in the effluent of R2 was higher than that in R1 at the end of stage I. In stage III, the relative abundance of Nitrolancea in R1 and R2 dropped to 0.43% and 1.06%, respectively. Nitrosomonas is a common AOB genus, and its abundance in R1 and R2 was 5.64% and 4.50%, respectively, in stage III. Fig. 20 It can be seen that the abundance of NOB species is much lower than that of AOB, which indicates that the activity of NOB was successfully reduced by gradually reducing aeration and gradually flushing it out of the reactor, successfully inhibiting the growth of NOB bacteria. CandidatusKuenenia and Nitrosomonas were enriched in the PN-A biofilm process, which is consistent with the previous analysis of the reactor effluent. It is worth noting that the number of AOB in the original carrier on R1 is greater than that in the composite carrier on R2. This is because most of the ecological niches on the composite carrier are occupied by AnAOB, and AOB only exist in a thin layer on the surface of AnAOB.

[0175] In summary, this example compares the performance differences between the reactor (R1) with the addition of a common polyurethane sponge carrier and the reactor (R2) with the addition of nZVI@Z-PU when starting the short-range nitrification-anaerobic ammonium oxidation process, in order to explore the effect of nZVI@Z-PU on the rapid start-up of the short-range nitrification-anaerobic ammonium oxidation process. By analyzing the experimental operation data for 116 days, the changes in the effluent quality and microbial activity of the two reactors were explored, focusing on the effects of different carriers on the rapid start-up of the short-range nitrification-anaerobic ammonium oxidation process. The effects of different carriers on the growth of microbial biofilms and changes in biofilm composition were also studied. In addition, the evolution process of the microbial community was also studied in depth, and the results are as follows:

[0176] (1) The R2 reactor with nZVI@Z-PU successfully started the short-cut nitrification-anaerobic ammonium oxidation process within 98 days, showing a significant treatment effect under low ammonia nitrogen concentration conditions. In contrast, the R1 reactor with ordinary polyurethane sponge carrier did not start the short-cut nitrification-anaerobic ammonium oxidation process until the 116th day after the end of the experiment. In summary, the reactor with nZVI@Z-PU showed excellent performance in starting the short-cut nitrification-anaerobic ammonium oxidation process for treating low-concentration ammonia nitrogen wastewater.

[0177] (2) nZVI@Z-PU has a stronger biomass fixation ability than ordinary polyurethane sponge carriers. Its MLVSS / MLSS ratio and the biomass of a single carrier are higher than those of ordinary polyurethane sponge carriers, showing higher biological activity. In addition, the PN / PS ratio in the EPS of nZVI@Z-PU increased significantly to 2.56, while that of ordinary polyurethane sponge carriers was only 1.75, indicating that nZVI@Z-PU has better film-forming properties. The bridging effect of Fe cations generated by nZVI in nZVI@Z-PU on PN leads to a significant increase in the content of PN in nZVI@Z-PU, which in turn promotes the formation of a stable agglomerate structure of the biofilm.

[0178] (3) At the bacterial phylum level, as NOB was eliminated and AOB bacteria were washed out in the reactor, the abundance of Proteobacteria and Chloroflexi decreased, while Bacteroidota continued to increase during the formation of the biofilm. At all stages of the experimental cycle, nZVI@Z-PU showed a higher abundance of Planctomycetes than ordinary polyurethane sponge carriers. At the end of the experiment, the abundance of CandidatusBrocadia in nZVI@Z-PU was significantly higher than that in ordinary polyurethane sponge carriers, indicating that AnAOB has a clear niche preference for nZVI-modified nZVI@Z-PU. nZVI@Z-PU creates a favorable local microenvironment, making it more suitable for the growth of short-range nitrification-anaerobic ammonium oxidation functional bacteria than ordinary polyurethane sponge carriers.

[0179] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a composite material of nano zero-valent iron and zeolite molecular sieve, characterized in that: The following steps are involved: The nano-zero-valent iron and the zeolite powder are uniformly mixed to obtain zeolite-nZVI powder; The zeolite-nZVI powder, waterborne polyurethane and PVA-polyquaternium salt-10 solution are mixed, and then impregnated, extruded, first dried, washed and second dried are performed in sequence to obtain the composite material of nano zero-valent iron and zeolite molecular sieve.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the nano zero-valent iron to the zeolite powder is 1:

8.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the zeolite-nZVI powder to the aqueous polyurethane is 27:

40.

4. The preparation method according to claim 1, characterized in that: The preparation method of the PVA-polyquaternium-10 solution comprises the steps of mixing a polyvinyl alcohol solution and a polyquaternium-10 solution to obtain the PVA-polyquaternium-10 solution; The mass percentage of polyvinyl alcohol in the polyvinyl alcohol solution is 10%; the mass percentage of polyquaternium-10 in the polyquaternium-10 solution is 5%; The volume ratio of the polyvinyl alcohol solution to the polyquaternium-10 solution is 10:

1.

5. The preparation method according to claim 1, characterized in that: The preparation method of the nano zero-valent iron comprises the following steps: (1) mixing FeCl3, water and a dispersant to obtain a pretreated FeCl3 solution; (2) subjecting the pretreated FeCl3 solution to ultrasonic treatment while introducing nitrogen to obtain a deoxygenated FeCl3 solution; (3) mixing KBH4, water and ethanol to obtain a KBH4 solution; (4) After mixing the KBH4 solution and the deoxygenated FeCl3 solution, stirring and standing the mixture in sequence to obtain the nano zero-valent iron.

6. The preparation method according to claim 5, characterized in that: In step (1), the mass volume ratio of the FeCl3, the water and the dispersant is 6g:50mL:2.5g; the dispersant is polyethylene glycol; In step (3), the mass volume ratio of KBH4, water and ethanol is 4.5g:20mL:30mL.

7. The preparation method according to claim 5, characterized in that: In step (2), the nitrogen gas introduction rate is 0.5 mL / min; In step (4), the stirring time is 1 hour, the rotation speed is 400 rpm; and the standing time is 30 minutes.

8. A composite material of nano zero-valent iron and zeolite molecular sieve prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the composite material of nano zero-valent iron and zeolite molecular sieve as claimed in claim 8 in sewage treatment.

10. Use of the composite material of nano zero-valent iron and zeolite molecular sieve as claimed in claim 8 in a rapid start-up short-range nitrification-anaerobic ammonia oxidation process.

Citation Information

Patent Citations

  • Smart membrane and preparation method thereof, membrane module, membrane bioreactor, and method for interception of microorganisms in water and sewage treatment method

    CN108014650A

  • Reinforced phosphorus removal composite filler as well as preparation method and application thereof

    CN116371383A

  • Super-hydrophilic self-repairing antifogging coating as well as preparation method and application thereof

    CN116921178A

  • Metal supported microorganism-immobilized carrier and treatment method for nitrogen-containing wastewater

    JP2004008923A

Cited By

  • Walnut shell photo-thermal conversion method based on molecular sieve coupling nanometer zero-valent iron

    CN120155442A

  • Combined enhanced denitrification device and method based on magnetic field-modified polyurethane composite material

    CN120208425A

  • A device and method for enhancing denitrification based on a magnetic field-modified polyurethane composite

    CN120208425B

  • Sulfur autotrophic-anaerobic ammonia oxidation coupled sewage deep denitrification system and method

    CN120364847A

  • Modification method and application of polyurethane filler for strengthening biochemical treatment of refractory industrial wastewater

    CN120774570A